Foreign Direct Investment, Technology Transfer, and Productivity Growth in Transition Countries Empirical Evidence from Panel Data - Elvisa Torlak (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2004)
Many governments offer significant inducements to attract inward investment, motivated by the expectation of spillover benefits. Foreign direct investment (FDI) is generally perceived as the best channel for technology transfer, not only across national boundaries but also between firms - in particular, between foreign and domestic companies. This paper tests this hypothesis for five transition countries in Eastern Europe using panel data on more than 8000 plants in the Czech Republic, Poland, Hungary, Romania and Bulgaria. In a log-linear model, the Cobb-Douglas production function is estimated to examine the productivity effect of: (a) foreign ownership in firms, and (b) foreign presence in industries and regions. In the first case, regression coefficients indicate a positive correlation between foreign equity participation and plant productivity. In the second case, the impact of foreign investment on productivity of domestically owned firms turns out to be either negative or insignificant. Thus, the study corroborates the hypothesis that technology is transferred internationally through multinational companies, but provides no evidence of diffusion of technology from foreign to domestic firms.
Keywords: P52; P31; F23; F21; F15; 330; foreign direct investment; transition; productivity; technology spillovers; Direktinvestition; Technologietransfer; Spillover-Effekt; Produktivität; Übergangswirtschaft; Schätzung; Tschechische Republik; Polen; Ungarn; Rumänien; Bulgarien